If tan ⁡ ( π 4 + y 2 ) = tan 3 ⁡ (...

Logan Wyatt

Logan Wyatt

Answered

2022-07-07

If tan ( π 4 + y 2 ) = tan 3 ( π 4 + x 2 ),then prove that sin y = sin x ( 3 + sin 2 x ) ( 1 + 3 sin 2 x )

Answer & Explanation

Nirdaciw3

Nirdaciw3

Expert

2022-07-08Added 20 answers

Now using Weierstrass substitution,
cos ( π 2 + A ) = 1 tan 2 ( π 4 + A 2 ) 1 + tan 2 ( π 4 + A 2 )
As sin A = cos ( π 2 + A ) applying Componendo and Dividendo
tan 2 ( π 4 + A 2 ) = 1 + sin A 1 sin A
Replace the values of tan 2 ( π 4 + y 2 ) , tan 2 ( π 4 + x 2 ) in
tan 2 ( π 4 + y 2 ) = tan 6 ( π 4 + x 2 ) = { tan 2 ( π 4 + x 2 ) } 3
and apply Componendo and Dividendo

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?